The Impact of Attractions and Accessibility on Visitor Motivation: A Case Study of Lampuuk Beach, Aceh Besar - Hasnaini, Hasnaini; Sumanti, Sumanti (Science and Environmental Journal for Postgraduate, 2024)
This study investigates the influence of attractions and accessibility on visitor motivation at Lampuuk Beach, Aceh Besar, Indonesia. Lampuuk Beach, known for its pristine white sand and surf-friendly waves, has seen a significant decline in visitors, with numbers dropping from 57,205 in 2018 to 7,906 in 2022. This decline is attributed to factors including the COVID-19 pandemic, economic challenges, and insufficient tourism infrastructure. Using a descriptive quantitative approach, this research analyzes data collected through accidental sampling of visitors at Lampuuk Beach. The study employs regression and path analysis, with attractions and accessibility as independent variables and visitor motivation as the dependent variable. Results reveal that attractions and accessibility collectively explain 88% of the variance in visitor motivation, with direct effects of 27.56% and 21.65%, respectively. Additionally, an indirect effect of 21.84% highlights the synergistic relationship between these variables. The remaining 28.95% is influenced by unexamined factors such as service quality and promotional efforts. This study underscores the critical roles of attractions and accessibility in driving visitor motivation, emphasizing the need for strategic improvements in these areas. Enhanced attractions and accessibility can bolster Lampuuk Beach's competitiveness as a premier tourist destination, ensuring sustainable growth and visitor satisfaction.